ANALYSIS OF THE INFLUENCE OF LOAD UNBALANCED ON NEUTRAL CURRENT IN FISHING VESSEL ELECTRIC GENERATOR CASE STUDY AT KM. PULAU PINANG - Bobby Demeianto; Hafiz Ziddin; Juniawan Preston Siahaan (Aurelia Journal, 2023)
Many studies have been conducted on load imbalance in 3-phase electrical installations, but research on the effects of unbalanced electrical loads on 3-phase electrical installations in fishing vessel generators has not been carried out. This study aims to determine the percentage value of load imbalance in the 3-phase electrical installations of KM fishing vessels in Pulau Pinang and observe its effect on the emergence of electric current in the neutral conductor cable in the electrical installation. The Indonesian Classification Bureau (BKI) in Volume IV rules for 2019 and 2022 regarding Electrical Installation on Ships requires that, under normal operating conditions, the percentage value of load imbalance in each phase must not exceed 15%. The research was conducted in three stages: March, April, and June 2021. From the study results, it was found that the average percentage value for load imbalance in KM Pulau Pinang on March 12, was 15.73% with an average electric current value of 8 Amperes in the neutral conductor. On April 7, the average percentage of unbalanced load sharing was 23.42% with an average neutral current of 12.26 Amperes. On June 19, the average percentage of unbalanced load sharing was 16.02% with an average neutral current of 6.11 Amperes.This research can provide new information regarding the study of load sharing imbalance and electric current in 3-phase electrical installations on fishing vessels. It can also serve as an evaluation for ship owners in reducing power losses due to the emergence of electric currents in the neutral conductor.